Anthropometric Comparison between Indian and Arabian Knees with Respect to Total Knee Replacement - Nair, Vijayamohan Sreedharan; Radhamony, Niranj Ganeshan; Padmalayam, Arjun; Govindan, Nijith O. (The Journal of Knee Surgery, 2020)
Implants used for total knee replacement (TKR) in most Asian countries are not designed originally for the Asian population, and studies have shown anthropometric differences with respect to TKR among various ethnic groups. For this reason, implants designed for a specific population may not provide an anatomic fit when used in other populations. To avoid the consequences associated with such a misfit, the concept of ethnic-specific implant design is being introduced. In this study, the knee anthropometry of the Indian and Arabian patients was compared. They were operated with implants which were not ethnic-specific designs. Since the consequences associated with implant misfit apply equally to both the Indian and Arabian population, it is essential to compare the knee anthropometry of these two populations. Anthropometric measurements of the distal femur and proximal tibia of the Indian and Arabian knees were obtained intraoperatively using a Vernier caliper. Their respective aspect ratios (ARs) were calculated and statistically compared. It was found that the ARs of both tibia and femur of Indian and Arabian population did not show any statistical difference. There was no statistical difference between Indian and Arabian males (p = 0.345) and between Indian and Arabian females (p = 0.8210). However, a statistical difference in tibial AR (p-value = 0.049) and femoral AR (p-value = 0.003) was found significant when a comparison was made between the knees of Indian males and Indian females in the study. The above results suggested that TKR implants designed anatomically to suit the Indian population can also suit the Arabian population and vice versa. The obtained data can help implant designers to come up with ethnic-specific TKR implants.
Keywords: anthropometry; morphology; proximal tibia; distal femur; aspect ratio; anteroposterior; mediolateral; Vernier caliper; Indian population; Arabian population; ethnic groups